Unrecognised myocardial infarction in patients with schizophrenia. Issue 2 (13th January 2015) - Nielsen, Jimmi; Juel, Jacob; Al Zuhairi, Karam Sadoon Majeed; Friis, Rasmus; Graff, Claus; Kanters, Jørgen Kim; Jensen, Svend Eggert
Abstract : Objective: Schizophrenia is associated with a reduction of the lifespan by 20 years, with type II diabetes and cardiovascular disease contributing the most to the increased mortality. Unrecognised or silent myocardial infarction (MI) occurs in 30% of the population, but the rates of unrecognised MI in patients with schizophrenia have only been sparsely investigated. Method: Electrocardiograms (ECG) from three psychiatric hospitals in Denmark were manually interpreted for signs of previous MI. Subsequently, ECGs were linked to the National Patient Registry in order to determine whether patients had a diagnosis consistent with previous MI. Results: A total of 937 ECGs were interpreted, 538 men (57.4%) and 399 women (42.6%). Mean age at the time of ECG acquisition was 40.6 years (95% CI: 39.7–41.5, range: 15.9–94.6). We identified 32 patients with positive ECG signs of MIs. Only two of these patients had a diagnosis of MI in the National Patient Registry. An additional number of eight patients had a diagnosis of MI in the Danish National Patient Registry, but with no ECG signs of previous MI. This means that 30 out of 40 (75%) MIs were unrecognised. Only increasing age was associated with unrecognised MI in a stepwise multiple logistic regression model compared with patients with no history of MI, OR: 1.03 per year of age, 95% CI: 1.00–1.06, p =0.021. Conclusion: Unrecognised MI is common among patients with schizophrenia and may contribute to the increased mortality found in this patient group.